Polarization of CO2 emissions in China's electricity sector: Production versus consumption perspectives. (20th March 2018) - Hou, Jianchao; Hou, Pengwang
Abstract: The inter-provincial inequality of per capita CO2 emissions in China's electricity sector means that their responsibilities for CO2 emission reduction are different. Considering the spatial separation of CO2 emissions in power production and consumption, with respect to the large scale inter-provincial electricity trade in China, this paper innovatively investigates the sub-national inequality and polarization degree of per capita CO2 emissions in China's electric power sector from the perspectives of both production and consumption. The overall tendencies of the sub-national polarization degrees of per capita CO2 emissions embodied in the both electric power consumption and production in China show an increasing trend. The results indicate that the polarization distribution of per capita CO2 emissions is still one of the important factors leading to difficulties in achieving the new reduction arrangements. The evolution of the bi-polarization analysis shows that the grouping results of per capita CO2 emissions are different from production and consumption perspectives, as well as the high- and low-emission groups have significantly different characteristics. The inequality and polarization degree of per capita CO2 emissions in China's electric power sector have changed as the CO2 emissions embodied in the electricity trade had been taken into account. One-Size-Fits-All Strategies are unlikely to be successful in advancing the provincial cooperation on CO2 emissions reduction. Highlights: The polarization of CO2 emissions in China's electricity sector is investigated. Analysis is from both production and consumption perspectives. Overall tendencies of the polarization degree show an increasing trend. Evolution of bi-polarization is analyzed. Polarization has changed when considering the CO2 emissions embodied in electricity trade.